ANALISIS PERAN PENGELOLA UNIT BISNIS DALAM PERENCANAAN STRATEGIS DAN UPAYA PENCAPAIAN KINERJA PERUSAHAAN (STUDI PADA INDUSTRI ENERGI LISTRIK DI JAYAPURA DAN ABEPURA) - Leonard J.F. Kbarek; Andarias Patiran (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2010)
Research this take title “Analysis Character Manager Units Business Inside Planning Strategy And Efforts Performance Corporation” (study Terapan On The Industrial Energy Electric In Jayapura and Abepura) as objek research is customer PT. PLN di Jayapura and Abepura, a number of 121 respondent.instrument analysis use in research is ‘structural equation modeling’ (SEM) where subject to change indogen laten in model this is intensityplanning strategic and performance company and statistical variable eksogen laten is factor managerial, factor environmental, and factor organizational manager encode do with support software Amos 5.01.Several innovation important from research this between its : all hypothesis raise accept, which cover hypothesis EKS1 to ENDO2, EKS2 to ENDO2, EKS3 to ENDO2 and ENDO2 to ENDO1 valuable positive meaning sence factor managerial in significant,influential positive to intensity planning strategic and also factor environment also in significance influential positive to intensity planning strategic and finally intesitas planning strategic influential positive and significance to performance company.Aspect managerial important for PT.PLN to pay attention some indicators in research this so that performance take care story first, to kontruk factor managerial pursuant to koefisien estimasi the is at kontruk, hence indicator become prioritas kebijakan his start from membership manager, catch up confidence manager and last profesionalitas staff.Limitation research this happened at instant encoding for processing, especiallyconcerning the duration time require to licensing, admission filling questioner and tabulation, remember is some reply at questioner which less consistent.